Avaliação e caracterização de insumos bioativos da aroeira (Schinus terebinthifolius Raddi) com potencial econômico para o desenvolvimento tecnológico de bioprodutos - Sales, Maria Diana Cerqueira (2013)
Aroeira (Schinus terebinthifolius Raddi) is an important plant mainly due its industrial application in the food industry, cosmetics and pharmaceutics. Since society has been exigent to choice qualified products, in this work we aimed identification and evaluation of bioactive products, such as mother tinctures (MT), extracts (Eb) and essential oils (EO) from leaves and fruits of aroeira genotypes. The TM were obtained from the leaves of plants hermaphrodite (TMArFH), female (TMArFF), and male (TMArFM) and fruits from hermaphrodite plants (TMArFrH) and two samples of female plants (and TMArFrF1 TMArFrF2), were prepared from the plant extract (with natural adjuvant) by maceration. OE from leaves (F01-F04) and fruits (the FR01- FR07), were obtained from the hydrodistillation. Analytical methods were used to perform physic-chemical analyses of MT and chemistry compounds identification were carried out by thin layer chromatography (TLC), high performance liquid chromatography (HPLC), gas chromatography (GC) and gas chromatography-Mass spectrometry (GC/MS). The antioxidant activity of the different MT was evaluated using the stable free radical DPPH (1, 1- diphenyl-2- picryl-hydrazyl) method and, evaluation of antifungal efficiency of TM was performed by the agar diffusion method, for the fungi Fusarium guttiforme and Chalara paradoxa, pineapple pathogens. The physico-chemical analysis showed average values of dry residue (1.41 ± 0.13%), alcohol content (67% ± 0.78), pH (5.6 ± 0.78) and density (0.898 g. mL-1 ± 0.98), within the technical specifications, indicating quality in the process and specifications to obtaining the TM. The chromatograms showed the presence of phenolic groups, especially, isolation of two important biflavonoids, agathisflavona and tetrahidroamentoflavona. Monoterpenes predominated, and the sample FR01, had the highest percentage of limonene (36.85%), which represented the highest relative content (70.85%). Regarding the antioxidant activity (AA), the TMArFH (250 µg/mL), showed better availability for uptake of DPPH (AA= 59.09%). In the antifungal test both TMArFH as tebuconazole fungicide at 0.1%, showed strong inhibition of the mycelial growth for F. guttiforme (PI= 82%) and a significant efficiency for C. paradoxa (PI= 42. 86%). This is the first report with the use of MT from leaves and fruits of S. terebinthifolius with potential feedstock for the development of bioproducts with fungicidal activity for control plant pathogens.